2011
DOI: 10.1249/jsr.0b013e318237bf74
|View full text |Cite
|
Sign up to set email alerts
|

Do Youth Sports Prevent Pediatric Obesity? A Systematic Review and Commentary

Abstract: Sport is a promising setting for obesity prevention among youth, but little is known about whether it prevents obesity. We reviewed research comparing sport participants with non-participants on weight status, physical activity and diet. Among nineteen studies we found no clear pattern of association between body weight and sport participation. Among seventeen studies we found that sport participants are more physically active than those who do not participate. Seven studies examined the relationship between s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
143
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(162 citation statements)
references
References 54 publications
(82 reference statements)
10
143
1
1
Order By: Relevance
“…A study that was conducted after the aforementioned review found that participation in sports teams protected adolescents from overweight and obesity 40 , a result which was contrary to that found in the present study. One aspect to be considered is that in both the systematic review 39 and in the present study, sports practice was considered on both the formal and informal levels, while in the study by Drake et al 40 sports practice was defined as as the amount of participation by young people in sports teams during the previous year. One characteristic that may explain the differences between these studies is that participation in sports teams is performed systematically and probably present higher volume of training.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…A study that was conducted after the aforementioned review found that participation in sports teams protected adolescents from overweight and obesity 40 , a result which was contrary to that found in the present study. One aspect to be considered is that in both the systematic review 39 and in the present study, sports practice was considered on both the formal and informal levels, while in the study by Drake et al 40 sports practice was defined as as the amount of participation by young people in sports teams during the previous year. One characteristic that may explain the differences between these studies is that participation in sports teams is performed systematically and probably present higher volume of training.…”
Section: Discussionmentioning
confidence: 98%
“…However, a systematic review gathered together studies that examined the association between sports practice with overweight and obese, and the results were inconclusive 39 . A study that was conducted after the aforementioned review found that participation in sports teams protected adolescents from overweight and obesity 40 , a result which was contrary to that found in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Sports participation has been inversely related to overweight/ obesity [1][2][3][4][5][6] with some variation by sport. 5,7 Elkins et al 7 found that football was associated with an increased risk of overweight/obesity, whereas basketball, track, and cheerleading were associated with a decreased risk of overweight/obesity. After Title IX' s passage (1972), which banned gender discrimination in academic and athletic programs, sports participation among high school girls increased by 600%.…”
mentioning
confidence: 99%
“…Current partnerships exist primarily for the purpose of generating profit and, as such, the majority of items available for sale within recreational facilities tend to be highly profitable, energy-dense, nutrient-poor items (2)(3)(4)(5)(6)(7) . Ready availability of unhealthy foods in recreational facilities and other sports venues may partially explain why a recent systematic review found that youth involved in sport consume more fast food, sugarsweetened beverages and energy, and have a similar weight status as non-participants (8) . Recommendations that children spend more time in recreational facilities to prevent obesity (9)(10)(11) may therefore be counterproductive if children consume snacks and meals in this setting.…”
mentioning
confidence: 99%